Renewable energy towards a greener environment - Thomson, George (Callisto Reference, 2015)
These books provide insight on the constantly evolving and demanding field of renewable energy. Energy resources are fast drying up and added to this is the problem of pollution. This book also takes a hard look at the reforms needed to make renewable energy resources our primary energy source. The future of an industry and civilization with renewable energy as its foundation is discussed here and will be helpful to those looking to research or learn about this field.